Research Progress on Electrospun Protein-based Nanofibers - Lingshuang RONG; Yuxin LI; Yungang CAO; Miaomiao LIU; Xin FAN (Shipin gongye ke-ji, 2022)
Protein can not only provide essential nutrition for human beings, but also have good processing properties and applications. Protein-based nanofibers are widely used in nutrition delivery, air filters, biomedicine, tissue engineering and other fields due to their high specific surface area. Electrospinning, as a simple, effective and low-cost method for the preparation of nanofibers, provides technical support for the further application of protein-based nanofibers. This paper reviews the preparation process, the fabrication conditions (flow rate, voltage, receiving distance, etc.) on fiber morphology, and the application of electrospun protein-based nanofibers (food industry, drug delivery, tissue engineering, air filtration). Finally, the potential research directions of protein-based nanofibers are prospected in order to provide reference for the controllable construction of electrospun protein-based nanofibers, the improvement of functional properties, and the industrial research and application of electrospinning.